ANALISIS KEMAMPUAN LITERASI MATEMATIS SISWA DALAM MENYELESAIKAN SOAL AKM DITINJAU DARI GAYA KOGNITIF REFLEKTIF IMPLUSIF - Putri, Qhory Amalia; Novaliyosi, Novaliyosi (Universitas Bhinneka PGRI, 2024)
The study aims to determine and describe students' mathematical literacy skills in solving AKM problems in terms of reflective and implusive cognitive styles. The subjects in this study were grade XI students at SMA Negeri 2 Pandeglang who had reflective and implusive cognitive styles. The method used is qualitative research with a descriptive approach. The selection of research subjects was carried out by purposive sampling technique based on using the cognitive style test instrument Matching Familiar Figure Test (MFFT). After that, a test was carried out to collect mathematical literacy skills by completing AKM questions and interviews. Analysis of mathematical literacy ability tests refers to three indicators of mathematical literacy, namely reasoning/argument, communication, and application/representation. Based on data analysis and discussion, it can be concluded that: (1) Students with refractive cognitive styles have medium category mamthematic literacy skills. (2) Students with implusive cognitive styles have low category mathematical literacy skills. The results showed that the mathematical literacy of students with reflective cognitive style was in the medium category with a percentage of 61.54%, while the mathematical literacy of students with cognitive implusive style was in the low category with a percentage of 57.14%.